Assessment of chemical risks and benefits connected with macroalgae consumption - Łukasz Woźniak; María Soledad Prats Moya (EFSA Journal)
Abstract Reducing animal‐based food production and consumption due to environmental issues and undergoing upcoming changes in food dietary patterns is pushing European society to search for new protein sources. Consuming macroalgae (seaweed) is one of the possible solutions, and it is an exciting alternative for both sustainability and consumers' health. The aim of this work, implemented under the EU‐FORA fellowship programme, was to evaluate the current and projected consumption of macroalgae in terms of possible beneficial and detrimental effects on consumers. The risk–benefit assessment methodology was selected as a tool for this task, and a broad range of qualitative analyses of raw material composition (e.g. fatty acids, micro‐, macroelements, heavy metals, biogenic amines). The current levels of macroalgae consumption in the EU are deficient; therefore, alternate scenarios using data from other countries and substitution scenarios are needed. Iodine turned out to be the most pivotal constituent – on the one hand; it is an element essential for life, often fortified in foods like milk or salt; on the other, its overdosing leads to serious thyroid complications. A very high variance in iodine levels between algal species was observed; therefore, it was suggested that this valuable knowledge is helpful in dietary recommendations.